MENHECÜ'L-EŞAIRA FI TEFSIRI AYATI SIFATI'LLAHI - ALI, BASHDAR R. MOHAMMED (Fırat Üniveristesi, 2017)
Allah Teâlâ'nın sıfatları hakkında konuşmak her Müslüman için çok önemlidir. Çünkü Allah'a iman iman, erkânının birincisidir. Allah'ın sıfatlarına iman da imanın bir cüzüdür. Allah Teâlâ Kur'an-ı Kerim'de kendisini kemal sıfatlarla nitelendirmiştir. Noksan sıfatlardan ise tenzih etmiştir. Sonra Hz. Peygamber (s.a.v) de ondan varid olan hadis-i şeriflerde Yüce Allah'ın celaline uygun vasıflarla vasıflandırmıştır. Sahabe-i Kiram da Kitap ve Sünnetteki yüce Allah'ın vasıflarına iman etmişler ve o vasıfların manalarını da anlamışlardır. Bu konuda Allah Resulüne soru sormamışlardır. Tabiun da onların yolunu izlemişlerdir. Allah'ın isim ve sıfatları konusunda aralarında hiçbir ihtilaf çıkmamıştır. Allah'ın sıfatları konusunda birbirleriyle asla tartışmamışlardır. Bilakis Kitap ve Sünnette varid olan hususlarda tam bir ittifak içinde olmuşlardır. Teşbih, temsil ve ta'tile sapmadan Allah'ın kendi nefsi için ispat ettiği ve Peygamberinin ispat ettiği bütün sıfatları kabul etmişlerdir ve ispat etmişlerdir. Sahabe-i Kiram Allah'ın kendi nefsi için ispat ettiği bütün sıfatları Arap dilinin gerektirdiği gibi tespit etmişlerdir. O halde biz de onların yolunu izleyerek Allah'ın kendi nefsi için tespit ettiği bütün sıfatları tespit etmeliyiz.

It is very important for every Muslim to talk about the attributes of Allaah. Because faith in Allah is the first of faith. Faith in the attributes of Allah is a part of faith. Allah has characterized himself in the Qur'an as adjectives. Allah has described himself as he deserves. Although, he has kept the inner of himself as clean about all imperfect characteristics. Then, the Prophet (s.a.v) has described the Almighty Allah in the hadiths that existed from it. Sahabe-i Kiram also believed the features of Almighty Allah in Quraan and Sunnah, and they also understood the meanings of those features. In this regard, they did not ask the Messenger of Allah. Of course they followed their path. There is no dispute between them concerning the names and attributes of Allah. They never discussed each other with regard to God's attributes. On the contrary, they are in complete alliance with the issues which exist in Quraan. They have accepted and proved all the attributes that Allah has proved for his own sake and proved by his prophet, without simmilarity to Allah, without representation, specification of modality and denying. Sahabe-i Kiram have identified all the attributes that Allah has proved for his own soul as the Arab language required. We must then follow their path and identify all the attributes Allah has established for his own soul.
Eşarilerin Allah'in sıfatlarıyla ilgili ayetleri tefsirdeki metodu
Keywords: Din